Assessment of the National Health Insurance Program in Nepal: Policyholders’ Experiences, Satisfaction, and Repurchase Intentions - Gautam, Prakash Kumar (Journal of Innovation in Academia, 2024)
The effectiveness of the public healthcare system indicates the nation’s socioeconomic prosperity and the National Health Insurance Program (NHIP) should be the cornerstone. This study explores policyholders’ experience, satisfaction, and repurchase intentions. It followed a quantitative approach with a causal-comparative research design using survey data from 403 policyholders from Gandaki and Lumbini provinces using convenience and snowball sampling. A five-point Likert scale was used to collect the data, which were analyzed using descriptive and inferential statistics to examine the mediation model. Results revealed moderate experience and satisfaction from the NHIP and examined the significant effect of policyholders’ experience on predicting policy repurchase intention. Further, the enhanced satisfaction from the policy benefits increases the impact of experience predicting repurchase intentions. This study contributes to the theory and practical implications of public health policy.